1997
DOI: 10.1002/cbm.146
|View full text |Cite
|
Sign up to set email alerts
|

Prison segregation: administrative detention remedy or mental health problem?

Abstract: This research was performed as a follow-up study of general psychological distress levels for inmates housed in restricted environments. Previous research has found increased levels of psychological distress in more restrictive environments, as measured by the global indices of the Brief Symptom Inventory (BSI). This study supported previous findings and found increased distress within three of the nine primary symptom dimensions of the BSI in the current conditions of a federal correctional institution and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Regarding depression and dysthymia, three studies with moderate quality evidence found higher scores in inmates having been exposed to SC (52)(53)(54). However, low quality evidence from two other studies (30,55) and one study with moderate quality evidence (51) did not observe differing depression scores between groups. Lower quality evidence was provided by studies which controlled for minimal (race and ethnicity) or no confounders and instructed inmates to self-report psychological symptoms (30,55).…”
Section: Systematic Reviewmentioning
confidence: 95%
“…Regarding depression and dysthymia, three studies with moderate quality evidence found higher scores in inmates having been exposed to SC (52)(53)(54). However, low quality evidence from two other studies (30,55) and one study with moderate quality evidence (51) did not observe differing depression scores between groups. Lower quality evidence was provided by studies which controlled for minimal (race and ethnicity) or no confounders and instructed inmates to self-report psychological symptoms (30,55).…”
Section: Systematic Reviewmentioning
confidence: 95%
“…Cohen, , 2008F. Cohen, , 2012Glaze & Herberman, 2013;Grassian, 2006aGrassian, , 2006bHaney, 1993Haney, , 2003Haney, , 2009Hayes & Rowan, 1988;Hresko, 2006;Kupers, 2008;Lovell, 2008;Metzner & Fellner, 2010;Miller & Young, 1997;P. S. Smith, 2008;Stephan, 2008).…”
Section: The Administrative Segregation Debatementioning
confidence: 99%
“…A national survey of prison wardens revealed that AS was generally seen as an effective practice for maintaining order and control by removing disruptive inmates from the general population (GP; Mears & Castro, ), yet research has consistently found adverse effects resulting from the use of AS (e.g., see Haney, ; Morgan et al ., ). Many of these studies have indicated that inmates placed in AS experience a myriad of mental health concerns and symptoms, including appetite and sleep disturbance, anxiety (including panic), depression and hopelessness, irritability, anger and rage, lethargy, psychosis, cognitive rumination, cognitive impairment, social withdrawal, and suicidal ideation and self‐injurious behaviours (see Andersen, Sestoft, Lillebaek, Gabrielsen, & Hemmingsen, ; Bonner, ; Cloyes, Lovell, Allen, & Rhodes, ; Cohen, , , ; Grassian, , ; Haney, , ; Hayes & Rowan, ; Hresko, ; Kupers, ; Lovell, ; Miller & Young, ; Smith, ; Way, Sawyer, Barboza, & Nash, ). While there appears to be a general consensus that AS is a less than ideal correctional policy, especially for vulnerable populations (e.g., juveniles, those with intellectual or mental deficits), it is the magnitude of harm caused by AS that has become a hotly contested issue.…”
Section: Introductionmentioning
confidence: 99%